Hepatic lesions in protein-deficient adult rats - Camargo, João Lauro Viana de [UNESP]; Angeleli, A. Y. O.; Burini, Roberto Carlos [UNESP]; Campana, A. O. (My University, 1978)
Four groups of 10 young adult Wistar male rats were fed ad libitum on a protein-free diet for periods of 7, 28, 56 and 84 days. Control groups were fed on a 20% casein diet. Food intake and body weights of rats were registered. Plasma protein levels and liver weight and fat content were determined. Sections of the caudate lobe were studied histologically. Fatty changes were classified in three grades. Protein-deficient rats exhibited loss of body weight and had low levels of plasma protein concentration. Liver lost weight after 7 days of protein deficiency; there was a gradual reduction in liver weight as periods of protein deprivation were longer. After 7 days, liver fat concentration was not significantly higher than in the respective control group; it was significantly higher in all the other malnourished animals, As periods of protein deprivation were longer, fatty changes became more severe. Other hepatic lesions were found in 5 of the 10 rats submitted to the longest period of protein deficiency. One of the rats showed a diffuse cellular atrophy, 2 animals showed an extensive haemorrhagic necrosis, another showed a focal area of reticulum collapse and the last exhibited a distortion of the normal architecture of the liver due to diffuse reticulum collapse and early nodular regeneration; these 2 last rats showed early fibrosis in portal areas. The findings suggest that other deficiencies may complicate the protein deficiency when rats are given a protein-free diet over prolonged periods. Even if the protein-deficient diet has protective nutrients, it may be that, when rats eat less food, as occurs in prolonged experiments deficiency of one or all of these elements can occur, depending on their relative amount in diet.
Keywords: animal experiment; etiology; histology; intoxication; liver; liver fat; liver toxicity; nutrition; protein deficiency; rat; theoretical study; Animal; Blood Proteins; Fatty Liver; Lipids; Liver; Male; Necrosis; Organ Weight; Protein Deficiency; Rats